In Silico Study of the Potential of Bioactive Compounds of Theobroma cacao as Antigingivitis Agents - Amalia Putri Lubis; Hidayanti Hidayanti; Rahadian Zainul; Iffat Syafiqoh Afif; Siti Amiroch; Mohammad Jamhuri; Mohammad Hamim Zajuli Al Faroby (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
This in silico study evaluated the antigingivitis potential of bioactive compounds from Theobroma cacao against matrix metalloproteinase-8 (MMP-8) (PDB ID: 5T35) using molecular docking and ADMET prediction. Molecular docking results showed that several compounds exhibited stronger binding affinities, indicated by lower docking scores, compared to the reference compound doxycycline. Among the evaluated ligands, 5,7-dihydroxy-3,4-dimethoxyflavone and procyanidin B1 demonstrated the most favorable binding interactions, primarily stabilized by hydrogen bonding and hydrophobic contacts within the active site. However, drug-likeness and ADMET analyses revealed that large polyphenolic compounds, particularly procyanidin B1, violated multiple pharmacokinetic criteria, suggesting limited oral bioavailability. In contrast, 5,7-dihydroxy-3,4-dimethoxyflavone showed an optimal balance between binding affinity and pharmacokinetic properties, with full compliance with Lipinski’s Rule of Five and Veber’s criteria, high predicted gastrointestinal absorption, and a favorable toxicity profile. Overall, this compound emerged as the most promising antigingivitis candidate from Theobroma cacao. These findings provide valuable molecular insights and support further experimental validation for the development of plant-based therapeutic agents targeting gingivitis..